Women and birth partners’ experiences of cervical ripening at home and in hospital - Cassandra Yuill; Mairi Harkness; Helen Cheyne; Boo Charkin; Monica Ferreira; Eloise Price; Amarnath Bhide; Mairead Black; Kathleen Boyd; Neelam Heera-Shergill; Neena Modi; John Norrie; et al. (BMC Pregnancy and Childbirth)
Abstract Background In the United Kingdom, induction of labour rates are rapidly rising, and around a third of pregnant women undergo the procedure. The first stage, cervical ripening, traditionally carried out in hospital, is increasingly offered outpatient – or ‘at home’. The current induction of labour rates place considerable demand on maternity services and impact women’s experiences of care, and at home cervical ripening has been suggested as potential solution for alleviating these. However, there is a lack of evidence on both women’s and birth partners’ experiences and acceptability of at home cervical ripening informing its practice. Methods We undertook a qualitative study of women and their birth partners’ experiences of cervical ripening at home and in hospital. Semi-structured interviews explored experiences, acceptability and consequences of cervical ripening. Results We identified six key themes: ‘Information and choice’; ‘Physical and sensorial environments’; ‘Pain’; ‘Uncertainty’; ‘Care during induction’; ‘Lasting effects’. Women and birth partners experienced limited choice about cervical ripening. Many reported that shared hospital spaces contributed to negative experiences, while home environments were comforting. Women were unprepared for cervical ripening-associated pain, and delays and uncertainty during induction caused anxiety. Supportive care contributed to more positive experiences; however, some reported difficult or traumatic experiences related to induction. Conclusions Most participants were positive about home cervical ripening, yet our study highlights the lack of information and genuine choice regarding cervical ripening and induction. Privacy, presence of birth partners and supportive care contributed to more positive experiences among women. Home cervical ripening may be acceptable to some women and birth partners in the context of informed choice and personalised care.